2006
DOI: 10.1111/j.1747-0080.2006.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in Australia and New Zealand: What are the dietary options?

Abstract: Measurement of serum vitamin D levels in population samples has revealed unexpectedly high prevalence of vitamin D deficiency among children, adults, the elderly and other vulnerable groups in Australia and New Zealand. The new Nutrient Reference Values report has established dietary recommendations for vitamin D of between 5 and 15 µg/day, depending on age. Dietary intakes of vitamin D in Australia typically fall in the range of 2–3 µg/day, below intakes in comparable countries. Dietary intake of vitamin D is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…This study was unique as a result of the multiple interventions used and showed that oral vitamin D 3 and Ca given daily were more beneficial at increasing BMD than injected megadoses of vitamin D 2 with or without oral Ca (75) . A second study by the Randomised Evaluation of Calcium oR vitamin D (RECORD) trial group (66) , however, showed no significant differences in incidence in low trauma secondary fractures for elderly participants on vitamin D 3 , Ca and vitamin D 3 or a placebo followed over 24-62 months (see Table 4).…”
Section: Intervention Studies Of Vitamin D's Role In Osteoporosismentioning
confidence: 99%
See 4 more Smart Citations
“…This study was unique as a result of the multiple interventions used and showed that oral vitamin D 3 and Ca given daily were more beneficial at increasing BMD than injected megadoses of vitamin D 2 with or without oral Ca (75) . A second study by the Randomised Evaluation of Calcium oR vitamin D (RECORD) trial group (66) , however, showed no significant differences in incidence in low trauma secondary fractures for elderly participants on vitamin D 3 , Ca and vitamin D 3 or a placebo followed over 24-62 months (see Table 4).…”
Section: Intervention Studies Of Vitamin D's Role In Osteoporosismentioning
confidence: 99%
“…Results showed that first fracture risk was reduced by 22 % in the intervention group, while fracture risk for common osteoporotic sites (hip, wrist and vertebrae) was reduced by 33 % (71) . Two trials using BMD as the endpoint, rather than fracture incidence, have also shown that vitamin D 3 and Ca supplementation or the use of vitamin D 3 -and Ca-fortified food products were associated with an increase in BMD (72,73) (see Table 4). Both of these studies had a number of weaknesses including the use of relatively low levels of supplemental and dietary vitamin D (7·5 -12·5 mg/d) and small subject numbers.…”
Section: Intervention Studies Of Vitamin D's Role In Osteoporosismentioning
confidence: 99%
See 3 more Smart Citations